2014
DOI: 10.1152/ajprenal.00605.2013
|View full text |Cite
|
Sign up to set email alerts
|

H-K-ATPase type 2: relevance for renal physiology and beyond

Abstract: H-K-ATPase type 2 (HKA2), also known as the “nongastric” or “colonic” H-K-ATPase, is broadly expressed, and its presence in the kidney has puzzled experts in the field of renal ion transport systems for many years. One of the most important and robust characteristics of this transporter is that it is strongly stimulated after dietary K+ restriction. This result prompted many investigators to propose that it should play a role in allowing the kidney to efficiently retain K+ under K+ depletion. However, the appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 87 publications
1
39
0
Order By: Relevance
“…2 Much evidence supports the role of the circadian clock in external homeostasis, and some evidence indicates a role in internal homeostasis. 7,12-14 …”
Section: Potassium Homeostasismentioning
confidence: 99%
“…2 Much evidence supports the role of the circadian clock in external homeostasis, and some evidence indicates a role in internal homeostasis. 7,12-14 …”
Section: Potassium Homeostasismentioning
confidence: 99%
“…An alternative or additional possibility would be active apical NH 4 + uptake via substitution on the K + site of H + /K + -ATPase, which has been identified in elasmobranch gills (Choe et al, 2004). NH 4 + is well known to be able to substitute for K + in a variety of transport systems, including members of this family of transport ATPases (Codina et al, 1999; Cougnon et al, 1999;Crambert, 2014).…”
Section: Research Articlementioning
confidence: 99%
“…An alternative or additional possibility would be active apical NH 4 + uptake via substitution on the K + site of H + /K + -ATPase, which has been identified in elasmobranch gills (Choe et al, 2004). NH 4 + is well known to be able to substitute for K + in a variety of transport systems, including members of this family of transport ATPases (Codina et al, 1999; Cougnon et al, 1999;Crambert, 2014).How relevant is the present ammonia exposure scenario to real world conditions? The water T Amm level used in our tests (1000 μmol l −1 ) was chosen for comparison to the many previous HEA studies on teleosts using a similar level, as cited above.…”
mentioning
confidence: 99%
“…, it is even closer to the ␣-subunit of gastric HKA (11). Furthermore, pharmacological profiles have suggested that rat nongastric HKA shares more similarities with rat Na (9), and the rabbit gastric ␤-subunit (rg␤HKA).…”
Section: Mathematical Model and Methodsmentioning
confidence: 87%